Oxidative Processing Lowers the Ice Nucleation Activity of Birch and Alder Pollen - Ellen Gute; Jonathan P. D. Abbatt (Geophysical Research Letters)
Abstract Pollen carry water extractable compounds with ice nucleating (IN) activity. This study investigates whether the hydroxyl radical, as the major atmospheric oxidant, can affect the IN activity of silver birch and grey alder subpollen particles under in‐cloud conditions for deposition freezing mode conditions at 234 K. It is found that oxidation increases the supersaturation ratio with respect to ice necessary for the onset of ice nucleation and decreases the fraction of particles which initiate ice nucleation. This reduction of IN activity under equivalent oxidation conditions does not occur with a mineral dust sample (Arizona Test Dust). Chemical analysis of fresh and oxidized pollen material indicates a change of molecular structure with a loss of conjugation and an increase in oxidized functional groups, such as carbonyls. This is the first demonstration that in‐cloud oxidation may lower the IN abilities of biological particles such as pollen.